Cooperation among primary exporters: A theoretical framework - Sugata Marjit (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
We study the possibility of cartel formation among primary exporters who face an inelastic world demand for their exports. By constructing an appropriate infinitely repeated export game, we show that varying country sizes will pose difficulties in sustaining the collusive behaviour.
Keywords: 330; Marketingkooperation; Rohstoff; Export; Spieltheorie; Theorie